2008
DOI: 10.1021/jm8006245
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of NF-κB Components by Covalent Binding of (−)-Dehydroxymethylepoxyquinomicin to Specific Cysteine Residues

Abstract: Previously, we designed and synthesized a potent NF-kappaB inhibitor, DHMEQ. Although DHMEQ showed potent anti-inflammatory and anticancer activities in animals, its molecular target has not been elucidated. In the present study, its target protein was found to be p65 and other Rel homology proteins. We found that (-)-DHMEQ bound to p65 covalently with a 1:1 stoichiometry by conducting SPR and MALDI-TOF MS analyses. MS analysis of the chymotrypsin-digested peptide suggested the binding of (-)-DHMEQ to a Cys re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
85
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 116 publications
(88 citation statements)
references
References 36 publications
(65 reference statements)
2
85
0
Order By: Relevance
“…It has been recently reported that (À)-DHMEQ covalently binds specific cysteine residues of Rel family proteins located closed to the DNA-binding sites (Cys-38 of p65, Cys-144 of Rel B, Cys-27 of c-Rel and Cys-62 of p50) (Figure 5b). 98 (À)-DHMEQ thereby blocks the DNA-binding activity of wild-type, but not mutated (Cys to Ser), Rel family proteins in their purified forms. 98 As for the bioactive epoxyquinoids, we have shown that (2R, 3R, 4S)-2,3-epoxy-4-hydroxy-5-hydroxymethyl-6-(1E)-propenyl-cyclohex-5-en-1-one (ECH, as shown in Figure 5a) and its structural derivatives specifically inhibit Fas-mediated apoptosis.…”
Section: Epoxyquinoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been recently reported that (À)-DHMEQ covalently binds specific cysteine residues of Rel family proteins located closed to the DNA-binding sites (Cys-38 of p65, Cys-144 of Rel B, Cys-27 of c-Rel and Cys-62 of p50) (Figure 5b). 98 (À)-DHMEQ thereby blocks the DNA-binding activity of wild-type, but not mutated (Cys to Ser), Rel family proteins in their purified forms. 98 As for the bioactive epoxyquinoids, we have shown that (2R, 3R, 4S)-2,3-epoxy-4-hydroxy-5-hydroxymethyl-6-(1E)-propenyl-cyclohex-5-en-1-one (ECH, as shown in Figure 5a) and its structural derivatives specifically inhibit Fas-mediated apoptosis.…”
Section: Epoxyquinoidsmentioning
confidence: 99%
“…98 (À)-DHMEQ thereby blocks the DNA-binding activity of wild-type, but not mutated (Cys to Ser), Rel family proteins in their purified forms. 98 As for the bioactive epoxyquinoids, we have shown that (2R, 3R, 4S)-2,3-epoxy-4-hydroxy-5-hydroxymethyl-6-(1E)-propenyl-cyclohex-5-en-1-one (ECH, as shown in Figure 5a) and its structural derivatives specifically inhibit Fas-mediated apoptosis. 99,100 Fas is a cell-surface receptor belonging to the TNF receptor superfamily and has a cytoplasmic death domain essential for the induction of apoptosis in a FADD-and caspase-8-dependent manner.…”
Section: Epoxyquinoidsmentioning
confidence: 99%
“…101 DHMEQ, a 5-dehydroxymethyl derivative of epoxyquinomicin C isolated from Amycolatopsis sp., is a unique NF-kB inhibitor that acts at the level of the translocation of NF-kB into the nucleus and DNA binding. 102,103 DHMEQ directly binds to NF-kB, and its effect is more potent on NF-kB with the activation domain (i.e., RelA, c-Rel and RelB) than on NF-kB without the activation domain (i.e., p50 and p52). We previously described the efficacy of DHMEQ on various lymphoid malignancies, including MM, CLL, ATLL, cHL and PEL.…”
Section: Ikk Inhibitorsmentioning
confidence: 99%
“…Because DHMEQ is quickly transported into cells and binds to NF-kB subunits within 15 min (42), inhibition of p65 phosphorylation by DHMEQ in the later phase may be caused independently of physical interaction between p65 and DHMEQ. To examine this possibility, p65-knockout (p65 2/2 ) MEF were transfected with wild-type p65 or C38S-mutated p65 that does not allow for binding of DHMEQ (11). The cells were then pretreated with DHMEQ, exposed to TNF-a, and subjected to Western blot analysis of Ser 536 -phosphorylated p65.…”
Section: Suppression Of Cytokine-triggered Nf-kb Activation By Dhmeq mentioning
confidence: 99%
“…A previous report suggested that DHMEQ directly bound to specific cysteine residues of NFkB subunits and suppressed their nuclear translocation and DNA binding (11). DHMEQ targets NF-kB more selectively than other known inhibitors (e.g., proteasome inhibitors) and therefore has advantages for therapeutic uses.…”
mentioning
confidence: 99%